URGENT HELP SOCIAL PARENT FAMILIES, DISABLED CHILDREN: ESSENCE AND TECHNOLOGY - Tatiana Victorovna Bakhutashvili (Вестник Северо-Кавказского федерального университета)
The article discloses the essence of emergency social assistance parent families, disabled children and characteristics of social support as a form of social service agencies that category that weak people.